Competition analysis using neighborhood models: implications for plant community assembly rules - Lopes, Sergio de Faria (Ethnobiology and Conservation, 2017)
Contemporary studies in plant ecology have investigated the processes and patterns underlying plant community of structure and dynamics, mainly in tropical forests. In this context, the effects of competitive interactions between trees and their neighbors on tree growth and survival in plant communities have been addressed using neighborhood models. The purpose of these efforts has been to better understand the processes that drive patterns of species abundance, which has the potential to change our understanding of the ecological and evolutionary factors involved in ecosystem dynamics. Therefore, studies concerning the competitive mechanisms that explain neighborhood interactions of plants are the subject of this short review. Two main ecological theories have received strong support in this regard: 1) environmental filtering and 2) niche complementarity. These theories are mutually compatible and act simultaneously, however, their relative importance may change depending on resource availability, type of plant community and successional stage.